Confiabilidad de las predeterminaciones cefalométricas en cirugía ortognática - Marín-B., Marta L.; Radi-L., José N.; Duque-S., Francisco L.; Echeverri-V., Juan D. (Revista Facultad de Odontología Universidad de Antioquia, 2020)
Surgical cephalometric prediction has been employed as a valuable diagnostic tool that gives the maxillofacial surgeon and his patients a visualized approach of the final results. This study measured the reliability of manually traced cephalometric surgical predictions of thirty three patients treated with orthognatic surgery. Surgical movement prediction tracing for each patient were made on presurgical lateral cephalometric radiographic films which were later compared with tracing made on post-surgical radiographs of the same patients. Reliability was determined by measuring the distance of soft and hard tissue cephalometric points between the superimposed tracings. Measurements were compared both horizontally (Frankfort Plane) and vertically (McNamara reference plane). Results showed that cephalometric surgical predictions have a higher degree of reliability for the maxillary and mandibular plane. On the contrary, menton prediction was more unreliable in general being the least in the sagital than on the vertical plane. These results are in agreement with those reported by other authors who also consider cephalometric prediction as a valuable tool for treatment planning.